2021
DOI: 10.3390/rs13081409
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Water Vapor Using Signals from Microwave Links below 25 GHz

Abstract: Water vapor is a key element in both the greenhouse effect and the water cycle. However, water vapor has not been well studied due to the limitations of conventional monitoring instruments. Recently, estimating rain rate by the rain-induced attenuation of commercial microwave links (MLs) has been proven to be a feasible method. Similar to rainfall, water vapor also attenuates the energy of MLs. Thus, MLs also have the potential of estimating water vapor. This study proposes a method to estimate water vapor den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In addition, deep learning methods have also been applied to water vapor estimation by CMLs. Song et al [104] trained an SVM model using prior data from RSL and water vapor density to mitigate the estimation error introduced by the process of extracting water vapor attenuation from RSL. Pu et al [105] achieved high temporal resolution (5-min) water vapor retrieval based on E-band CMLs using an LSTM deep learning model.…”
Section: Monitoring Phenomena Related To Water Vapormentioning
confidence: 99%
“…In addition, deep learning methods have also been applied to water vapor estimation by CMLs. Song et al [104] trained an SVM model using prior data from RSL and water vapor density to mitigate the estimation error introduced by the process of extracting water vapor attenuation from RSL. Pu et al [105] achieved high temporal resolution (5-min) water vapor retrieval based on E-band CMLs using an LSTM deep learning model.…”
Section: Monitoring Phenomena Related To Water Vapormentioning
confidence: 99%
“…In addition, CML-based measurement can estimate not only rainfall, but also water vapor, solid particles, fog, snow, sleet, hail, and so on [26][27][28][29].…”
Section: Basic Principlementioning
confidence: 99%
“…Recent studies have shown the potential and the ability of harnessing the CML at high frequencies (E-bands) which are more sensitive to the changes of humidity but are often shorter, and thus are not always compatible for humidity detection [13,14]. In addition, research on the ability to measure the humidity based on low CML frequencies was also performed [15]. This study emphasizes the potential of the cellular infrastructure to provide large amounts of data which can potentially be used as humidity observations at a high temporal and spatial resolution.…”
Section: Introductionmentioning
confidence: 99%